The Founding Father of Chinese Animation ——An Exploration of Wan Laiming's Animation Creation and Design Philosophy (Journal of Global Arts Studies, 2024)
Background: After a century of development, Chinese animation has reached a new starting point. The pioneering efforts and creative philosophies of early animators have become valuable assets for contemporary Chinese animation, as it seeks to engage both the present era and the global stage.Objective: To explore the animation creation and design philosophy of Wan Laiming, a pioneer and key founder of Chinese animation, with the aim of providing insights and references for the practice and development of Chinese animation in the new era.Methods: By searching and reviewing a vast array of relevant literature, this study briefly reviews Wan Laiming's artistic life and his exploration of the art of animation, analyzing the design philosophy he developed in his animation creations.Results: It is pointed out that Wan Laiming's animation creation and design philosophy can be divided into three aspects: "National Independent Technical Approach," "National Self-Confident Artistic Form," and "National Self-Strengthening Path Practice."Conclusion: The study concludes that Wan Laiming's animation creation and design philosophy has had a significant impact on the nationalization development of Chinese animation and still holds important enlightening significance for the contemporary development of Chinese animation.
Keywords: All Sounds Silent; Chinese Animation; Creative Design Thought